The Concept Of Musyarakah In Ahkam Tafsir And Hadith - Ritonga, Marataon; Yuslem, Nawir; Jamil, M (Al-Fikru: Jurnal Ilmiah, 2025)
Musyarakah is one of the cooperative agreements in Islamic economics that has a normative basis in the Qur’an and hadith. However, differences in interpretation of the verses of ahkam and the quality of the hadith used as a legal basis often lead to debates in the determination of laws and their implementation in contemporary sharia economic practices. The main issue in this study is how the basis of interpretation and hadith ahkam on musyarakah and the methods of istinbat law used by scholars in determining its permissibility. This study uses a qualitative method with a normative-doctrinal approach through library research, analyzing verses from the Qur’an, hadiths on muamalah, books of tafsir ahkam, and classical and contemporary fiqh literature. The results of the study show that musyarakah has strong shar’i legitimacy, even though some of the arguments are implicit and require contextual interpretation. Authentic hadith and hadith whose sanad are disputed substantially emphasize the importance of honesty, trustworthiness, and fairness in business cooperation. The differences in views among the madhhabs regarding musyarakah are methodological in nature and do not negate its permissibility. With the maqāṣid al-syarī‘ah approach, musyarakah remains relevant and applicable in modern Islamic economics as long as it is carried out in accordance with the principles of justice and shared responsibility.